2014
DOI: 10.1002/adfm.201304230
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Computational‐Experimental Approach to Improve Ionene Polymer‐Based Functional Hydrogels

Abstract: The manifold applications of ionene‐based materials such as hydrogels in daily life, biomedical sciences, and industrial processes are a consequence of their unique physical and chemical properties, which are governed by a judicious balance between multiple non‐covalent interactions. However, one of the most critical aspects identified for a broader use of different polyelectrolytes is the need of raising their gelation efficiency. This work focuses on surfactant‐free ionene polymers 1−3 containing DABCO and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 47 publications
2
37
0
1
Order By: Relevance
“…In our previous work, we demonstrated a remarkable influence of the substitution pattern on the central benzene ring (i.e., para -, meta -, ortho -) on the hydrogelation [32] and dye uptake properties [34] of some of these polymers. In this study, the antimicrobial activity against the Gram-negative bacterium Escherichia coli has been determined for a library of 13 ionenes with different topologies and diamine linkers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demonstrated a remarkable influence of the substitution pattern on the central benzene ring (i.e., para -, meta -, ortho -) on the hydrogelation [32] and dye uptake properties [34] of some of these polymers. In this study, the antimicrobial activity against the Gram-negative bacterium Escherichia coli has been determined for a library of 13 ionenes with different topologies and diamine linkers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In both cases catalyst quantities of 0.5-1 mol% allowed us to reach conversions of more than 50% after 4 h reaction time (120 °C), and almost complete conversion when doubling the reaction time in the presence of 0.5 mol% D 1,4 (entry 14). In addition, also the cyclohexyl-based polymer E and the pyridiniumbased F showed some promising initial catalytic potential (entries 15,16).…”
Section: Resultsmentioning
confidence: 99%
“…ortho-, meta-, para-) in some of these polymers was found to play a key role on the hydrogelation [15], dye uptake [16] and antimicrobial properties [17]. In addition, our groups and others have shown that these versatile polymers can also serve as easily recoverable and reusable phase-transfer catalysts for a variety of different transformations [18][19][20].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thinking in a new family of bioactive platforms based on PEDOT-collagen biocomposites (hereafter denoted P(EDOT:CLG), in this work we used an experimental-computational approach that was proven to be successful for the development of advanced functional materials. 34,35 First, the P(EDOT:CLG) has been prepared and characterized as bioactive matrix for cell adhesion and proliferation. After such experimental characterization, specific interactions between the building blocks of the two components of this biocomposite have been investigated using ab initio quantum mechanical (QM) calculations and hybrid quantum mechanical/molecular mechanicalmolecular dynamics (QM/MM-MD) simulations.…”
mentioning
confidence: 99%